Pengaruh Pendapatan terhadap Produktivitas Pelaku Usaha Mikro di Kelurahan Karyamulya Kecamatan Kesambi Kota Cirebon - Sastrawardana, Viqia; Nabilah, Amelia; Fatur Rochma, Rizkia (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2025)
Productivity refers to the efficiency with which goods and services are produced, measured using the ratio of outputs produced to inputs in the production process. Micro business actors are individuals or groups that run businesses using a small scale, with limited capital and turnover. This research is located in Karyamulya Village, Kesambi District, Cirebon City regarding micro business actors. This research method uses descriptive quantitative and data collection with a questionnaire, and uses a sample technique, namely census sampling (saturated sample) of 34 samples. In this study, using the SPSS (Statistical Package for the Social Sciences) version 30.00 application to analyze data from respondents. The results of the discussion in this study are 26.23% of the variables of this study, while 73.77% of other variables must be studied. So this study stated that there is a correlation between income and productivity variables in micro business actors.